The Effect of a Learning Program According to the Felder and Silverman Model Using Assistive Aids to Develop Reflective Thinking and Learning Some of Basic Skills for Students in Tennis - Makarim Aliawi Nasser (Journal of Global Pharma Technology, 2016)
The importance of the research is the need for the teacher to search for the best method that is appropriate to the nature of the student and his educational environment in a manner that motivates the student and to achieve the best performance, and this through the preparation of an educational program using the model Feldder and Silverman aims to develop their thinking and learn some basic skills in tennis as well as use The aids that contribute to and accelerate the acquisition of skills and facilitate their performance because they give a clear impact in learning the basic skills that represent the ultimate goal of the learning process. The purpose of the research is to: Prepare an educational program according to the Felder and Silverman model using the aids in the development of intellectual thinking and learning some basic skills for students, to know the effect of the educational program according to the Feldder and Silverman model in the development of thinking and learning some basic skills for students. According to the model of Felder and Silverman using the aids in the development of intellectual thinking and learning some basic skills in tennis for students.The Research HypothesesThere are statistically significant differences in the development of reflective thinking and learning some basic skills for students between the tests of pretest and posttest, there are significant statistical differences between the groups research in posttest tests. The researchers used the experimental program to design the equivalent groups with pre and remote testing because it fits in with the research problem. The research community determines the students of the third stage - the College of Physical Education and Sports Sciences / Karbala University for the academic year 2017-2018 (96) (A-B-C-D) The research sample was selected by lot. The sample of the research was the students of the (A-B) division, where the number of A (23) students and (B) (27) The Feldder and Silverman scale applied to the research sample of the students of the two divisions, and the researchers reached the following conclusions: The educational program developed according to the model of Felder and Silverman for learners has had a clear and effective effect in the development of intellectual thinking and learning some basic skills of tennis for students, the educational program helped to master each part of the skills and the emergence of development of the skill level of the two experimental groups in the development of contemplative thinking and skills. The recommendations were as follows: The need to focus on the use of methods Felder and Silverman through the use of teaching aids because it accelerates the process of learning, the need to rely on the principle of classification of students according to the model Felder and Silverman before embarking on any research, the need to conduct similar studies and the use of samples and other skills.Keywords: Learning program, Felder and Silverman model, Reflective thinking and tennis.